Barriers and Facilitators for Physical Activity in Older Adults - Jahanvi Dineshbhai Patel; Megha Sheth; Anjali Jain (Journal of Integrated Health Sciences)
Background: Physical activity (PA) has many benefits in preventing diseases and is essential for maintaining physical and mental well-being. Even so, only a few older people regularly participate in PA. Both facilitators and barriers affect physical exercise in older people. Aim: This study aims to find barriers and facilitators of PA in older adults. Materials and Methods: This observational study used face-to-face interviews to gather data from older people (age >60 years) of a community of Ahmedabad. A set of questions was prepared to identify facilitators and barriers to PA in older adults. Data were collected from 150 older people through the convenience sampling method. Statistical Analysis: Descriptive statistics was used. Results: One hundred and fifty participants with a mean age of (67.92 ± 5.95) years participated in the study, including 71 (47.3%) females and 79 (52.7%) males. The results show that the common barriers to PA in older adults are health problems (31.7%), lack of time (30.2%), lack of motivation (46%), and weather (38%). Facilitators are beliefs that PA may prevent health problems (81%), improve health conditions (81%), enjoyment of activity (63.5%), family and friends’ involvement (47.6%), having the opportunity for PA-related support and social interaction with the participants (61.9%), living in a walkable area (60.3%), convenient/nearby PA locations (50.8%), and even walking surfaces (63.5%). Conclusion: Barriers to PA in older people were health problems, a lack of time, a lack of motivation/laziness, a lack of guidance from a professional, weather and environment such as traffic and lack of green areas. Facilitators believed that PA may prevent health problems; having the opportunity for PA-related support and social interaction/participation, living in a walkable area, even walking surfaces, and enjoyment of PA were also facilitators for PA among older adults.